PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN MULTIREPRESENTASI SISWA KELAS X MAN 1 PEKANBARU PADA MATERI USAHA DAN ENERGI - Ulfia Perdani; Fakhruddin Z Fakhruddin Z; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to determine the influence of guided inquiry model learning to student multiple representations ability on work and energy subject. The kind of this study was a quasy experimental approached by using intact group comparison design. The population in this study was students grade X MIA MAN 1 Pekanbaru which consisted of four classes. Two classes were selected as the sample of this study based on normality and homogeneity test so that experimental and control class could be obtained. The data was collected by given a test about multi representation ability. The data was analyzed by using descriptive and inferential statistic techniques. The result of this study shows that there was significant influence to multiple representations ability between experimental class which applied guided inquiry model learning and control class which applied conventional learning model. The multirepresentation ability of the experimental class is higher than control class. Based on data analysis, it can be concluded that the guided inquiry learning model has a positive effect on the multiple representation ability of the students.Keywords : Guided inquiry model learning, multiple representations ability, work and energy